Effectiveness Of Educational Packages on Knowledge and Practices Regarding Substance Use Disorders - R. Sree Raja Kumar; Azra Khan; Supriya Awasthi (Revista Electronica de Veterinaria, 2024)
Introduction: Individuals often seek substances for positive emotions, relaxation, or vitality, but substance use can cause severe health issues, stigma, and family distress. Academic programs must address substance misuse, providing information on therapies and treatment facilities. Prioritizing substance use education in schools and public health initiatives is crucial, emphasizing its harmful effects and addiction. Recognizing a knowledge gap, the researcher chose to study this issue to ensure nursing students receive proper training to manage substance use disorders effectively.Objectives: The study will assess the impact of educational packages on substance use disorder prevention and management by measuring changes in knowledge and practices among final-year nursing students using a knowledge questionnaire and a scenario-based questionnaire.Methodology: This quantitative non-randomized control trial assessed the impact of educational packages on substance use disorder prevention and management among B.Sc. Nursing IV Year and GNM III Year students at Nightingale College of Nursing (intervention) and Sharda School of Nursing (control). Multistage sampling selected colleges, and purposive sampling recruited students. Data collection instruments included validated socio-demographic profiles, knowledge questionnaires, and scenario-based practice questionnaires. The study, approved by the Institutional Ethics Committee, ensured informed consent and confidentiality. The intervention group received educational packages, with pre- and post-tests conducted to measure knowledge and practices. Data were analyzed using EZR software.Results: Mean age was 21.5 ± 0.8 years in the interventional group and 21.2 ± 2.5 years in the control group. The interventional group’s mean knowledge scores increased significantly from 14.7 (SD 5.1) to 28.4 (SD 3.6), with a mean difference of 13.6 (p < 0.001). The control group’s scores also rose from 14.2 (SD 4.8) to 16.2 (SD 4.2), with a mean difference of 2.0 (p < 0.001). Similarly, the interventional group’s mean practice scores improved from 11.2 (SD 4.5) to 19.4 (SD 2.4), a mean difference of 8.1 (p < 0.001), while the control group’s scores increased from 10.1 (SD 3.9) to 12.1 (SD 3.6), a mean difference of 2.0 (p < 0.001). These findings show significant knowledge and practice improvements in both groups.Conclusion: The interventional group showed greater improvement in practice scores compared to the control group after receiving educational packages on substance use disorder, management, and prevention. However, enhancing knowledge and practices depends on adherence to guidelines and the perceived benefit of the intervention. As educational systems adopt innovative strategies, this study encourages healthcare and educational organizations to develop novel methods for implementing educational packages to enhance nursing students' knowledge and skills in daily practice.